The Use of Mendeley Application to Avoid Plagiarism: A Case Study in Indonesia’s Tertiary Educatio - Sharizan Sharizan; Alissa Rahmasari; Kheisen Eiden; Yuyun Yulia; Rozanah Katrina Herda; Elizaveta Ivashova (Wahana Pendidikan, 2025)
The Mendeley and other automatic citation applications are used to help make the writing process more effective and avoid plagiarism. It is used massively in this digital age. Then, this case study aims to explore the motives behind plagiarism and the role of the Mendeley application and other online tools in avoiding plagiarism in Indonesia’s tertiary education. The primary data was gathered by interviewing five master's students from one of the public universities in Indonesia. Then, the data is processed by transcribing, coding, selective, and axial coding. The results show five primary motives for plagiarism based on the interview: the lack of awareness and understanding of plagiarism, negative personal attitude, the ease of internet access, pressure from several aspects, lack of competency, and institutional factors. In terms of the role of Mendeley's application to avoid plagiarism, it is adequate to confirm, justify, and claim the issue conveyed in scientific work, highlight a particular idea, criticize or approve the premise of others, and build the argument. It can be concluded that there are various reasons scholars commit plagiarism, and the Mendeley application, as well as some other artificial intelligence tools, can help to avoid it. However, scholars need to uphold academic integrity and understand the use of the Mendeley application for educational purposes